Stream flow alone does not predict population structure of diving beetles across complex tropical landscapes. Issue 17 (3rd August 2018) - Lam, Athena; Toussaint, Emmanuel F. A.; Kindler, Carolin; Van Dam, Matthew H.; Panjaitan, Rawati; Roderick, George K.; Balke, Michael
Abstract: Recent theoretical advances have hypothesized a central role of habitat persistence on population genetic structure and resulting biodiversity patterns of freshwater organisms. Here, we address the hypothesis that lotic species, or lineages adapted to comparably geologically stable running water habitats (streams and their marginal habitats), have high levels of endemicity and phylogeographic structure due to the persistent nature of their habitat. We use a nextRAD DNA sequencing approach to investigate the population structure and phylogeography of a putatively widespread New Guinean species of diving beetle, Philaccolilus ameliae (Dytiscidae). We find that P. ameliae is a complex of morphologically cryptic, but geographically and genetically well‐differentiated clades. The pattern of population connectivity is consistent with theoretical predictions associated with stable lotic habitats. However, in two clades, we find a more complex pattern of low population differentiation, revealing dispersal across rugged mountains and watersheds of New Guinea up to 430 km apart. These results, while surprising, were also consistent with the original formulation of the habitat template concept by Southwood, involving lineage‐idiosyncratic evolution in response to abiotic factors. In our system, low population differentiation might reflect a young species in a phase of range expansion utilizing vast available habitat. We suggest that predictions of life history variation resulting from the dichotomy between lotic and lentic organisms require more attention to habitat characterization and microhabitat choice. Our results also underpin the necessity to study fine‐scale processes but at a larger geographical scale, as compared to solely documenting macroecological patterns, to understand ecological drivers of regional biodiversity. Comprehensive sampling especially of tropical lineages in complex and threatened environments such as New Guinea remains a critical challenge.